Food Leftover Practices among Consumers in Selected Countries in Europe, South and North America - Koppel, Kadri; Higa, F.; Godwin, S.; Gutierrez, N.; Shalimov, R.; Cardinal, P.; Di Donfrancesco, B.; Sosa, M.; Carbonell-Barrachina, A. A.; Timberg, L.; Chambers, Edgar, IV (My University, 2017)
Foodborne illnesses may be related to many food production factors with home practices of consumers playing an important role in food safety. Consumer behavior for handling food leftovers has been studied, however little work on comparisons among countries has been published. The objective of this study was to investigate home food leftover practices of people from North American, South American, and European countries. Surveys were conducted with approximately 100 or more consumers in Argentina, Colombia, the United States, Estonia, Italy, Russia, and Spain. The participants responded to questions related to the length of time different types of food leftovers; such as meat, fresh salads, or restaurant dishes would be kept refrigerated or would be left at room temperature before refrigeration. Researchers also investigated how consumers would determine if the food was still safe for consumption. Potentially risky behaviors were observed in all seven countries. For instance, 55.8% of Estonians, 25% of Russians and 25.8% of Argentinean participants left food out at room temperature for several hours before storing in the refrigerator. Furthermore, 25%-29% of Colombian, Estonian, and Spanish consumers would look, smell, and taste leftovers to determine its probable safety. Correct handling of leftovers is an important aspect of consumer food safety. Although the surveys cannot be representative of all consumers in each country, they do provide an initial overview of comparative practices for handling leftovers among different countries. This provides government and educators with information on potential universal and unique consumer food safety issues related to handling leftover foods among various countries.
Citation: Koppel, K., Higa, F., Godwin, S., Gutierrez, N., Shalimov, R., Cardinal, P., . . . Chambers, E. (2016). Food Leftover Practices among Consumers in Selected Countries in Europe, South and North America. Foods, 5(3), 14. doi:10.3390/foods5030066
Keywords: Consumer; Cross-Country; Food Safety; Leftovers; Consumption; Behaviors